Historiografi Tafsir - Anisa Cikal Rambu Basaey; Kusnadi Kusnadi; Pathur Rahman (Penerbit Hellow Pustaka, 2026)
The historiography of exegesis is a field of study that examines how the history of the development of Qur’anic exegesis has been written, compiled, and constructed across various historical periods. This field is important because the history of exegesis not only documents the development of exegetical works and the lives of exegetes but also reveals the intellectual, social, political, and cultural dynamics that have influenced the emergence of various interpretive approaches. This article aims to analyze the methods used in writing the history of exegesis, identify the influence of ideological biases in the historiography of exegesis, and explain the periodization of exegetical development in the Indonesian archipelago. The research employs a library research method with a descriptive qualitative approach. Data were obtained through a review of various relevant literature, including books, scholarly articles, and research findings on historiography and the study of exegesis. Data analysis was conducted through data reduction, classification, interpretation, and the drawing of conclusions using a descriptive-analytical approach. The results of the study indicate that the historiography of tafsir has been developed through several approaches, namely chronological, biographical, thematic, and contextual-historical. The writing of the history of exegesis is also not entirely value-free, as it is influenced by the author’s ideological background, which has the potential to give rise to different historical constructions. Furthermore, the development of exegesis in the Nusantara has undergone a transformation that can be understood through several periods from the early, medieval, modern, to contemporary periods which demonstrate the increasingly strong efforts to contextualize exegesis in line with societal developments. Thus, the historiography of exegesis serves not only as a reconstruction of the history of Qur’anic interpretation but also as a means of understanding the dynamics of the development of Islamic thought from one era to the next.